Pengaruh Pengetahuan dan Sosialisasi Pajak terhadap Kepatuhan Wajib Pajak UMKM dengan Kesadaran sebagai Variabel Intervening - Sri Damai Simanjuntak; Vebry M Lumbangaol; Herti Diana Hutapea (Jurnal Minfo Polgan, 2025)
Low taxpayer compliance in Indonesia, despite the increasing number of Micro, Small, and Medium Enterprises (UMKM), is still a problem, especially in remote areas such as North Tapanuli. Many UMKM do not understand their tax obligations, which results in low levels of compliance. Knowledge of tax rules and procedures among them is also very minimal. In addition, the socialization carried out by the government has not reached all taxpayers, so that understanding of the importance of taxes and their impact on development is still low. This study aims to determine the effect of tax knowledge and socialization on compliance, with taxpayer awareness as an intervening variable, especially among UMKM in Tapanuli Utara. The quantitative method with Partial Least Square (PLS) analysis was used in this study. The results show that taxpayer knowledge has a positive effect on compliance, as does tax socialization. However, knowledge does not affect taxpayer awareness, while socialization has a positive effect. Taxpayer awareness affects compliance and acts as a mediator between socialization and compliance, but not between knowledge and compliance. This study emphasizes the importance of increasing tax knowledge and socialization to encourage taxpayer awareness and compliance among UMKM, with recommendations for the Regional Revenue Agency to expand more accessible tax education programs.